The Der Text als existenziale Kategorie: expliziert am Beispiel der Textsorte "autobiographisches Notat" - Fabčič, Melanija Larisa (2003)
Text as an Existential Category:  Explicated Using the Example of the Text Type "Autobiographical Notat". No abstract.